الدراسة الأسلوبية: تحليل أسلوب السخرية والتهكم والهجاء في مسلسل بهلول أعقل المجانين الجزء الأول - Rahmat Zatnika, Aziz (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
After 2022, people's trends will have changed with the times. Watching films will become a new lifestyle in our society. Films have a diverse impact on society and are a means of conveying messages that are easily accepted, but understanding a film also requires sufficient insight. Stylistics is a way of greeting something to achieve what is intended; understanding stylistics will support understanding when watching movies. The first season of